Testing brand equity dimensions of bank brands, consumer behaviour and firm financial performance - Masunu, Mwasi Raiya (Mzumbe University, 2026)
A dissertation submitted to Mzumbe University (DCC) as a partial fulfilment of the requirement for the award of Master's Degree of Applied Economics and Business of Mzumbe University